POLYMORPHIC SITES IN FACTOR X GENE - Chelucci, C; Hassan, H J; Guerriero, R; Leonardi, A; Mattia, G; Peschle, C (Thrombosis and Haemostasis, 1987)
The structure of factor X gene has been analyzed by Southern blot in 5 subjects with factor X deficiency.Genomic DNA was digested with 8 different endonucleases and hybridized with a cDNA probe. The congenital deficiency observed in these patients is not apparently due to a major deletion or rearrangement. Since the gene locus is grossly intact, the disease presumably results from point mutation(s) not identified by the utilized endonucleases.Our study was also focused on the presence of polymorphic site(s) in the factor X gene locus. Analysis of 50 normal subjects allowed to identify several polymorphic restriction sites after digestion with EcoRI, Hind III and Pvu II.The restriction pattern obtained after Hind III digestion showed two bands of 7.3 and 6.0 Kb, while in two families an additional 7.6 Kb band was observed. Genomic DNA digested with EcoRI showed a 7.1 and 5.1 Kb fragments, and also a 6.6 Kb band with a 10% f requency.After DNA digestion with Pvu II 5.6, 2.7 and ∼1.0 Kb bands were observed. In three unrelated subjects we observed an additional 3.0 Kb fragment, in two other subjects a 3.5 kb band. Interestingly hybridization with a 178 bp cDNA subclone allowed to map the polymorphic sites in a the 3’ region of the gene locus.